Editorial - Gómez Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2020)
As is widely known, in recent years the impact factor of scientific journals has been the main indicator of their quality, based on the premise that a citation isa quality reference.